PROGRAM STRATEGI PEMANFAATAN WILAYAH PESISIR DI DESA LAIKANG, KABUPATEN TAKALAR - Farida Patittingi; Marwah; Amaliyah; Andi Kurniawati (LP2M Universitas Hasanuddin, 2022)
The community's lack of understanding about the rules of coastal boundaries and how to manage and use coastal areas has led to many conflicts between residents. Meanwhile, awareness of the strategic values of managing coastal areas in a sustainable, integrated and community-based manner is also very lacking.The purpose of this service activity is to increase public understanding regarding the management and utilization of coastal areas so as to minimize disputes that lead to conflicts between residents. The method used is the method of legal counseling by presenting direct sources from the Land Office of Takalar Regency and academics who are experts in Coastal Area Management. The level of success of the activity was measured by the existence of a questionnaire in the form of pre-test and post-test given to participants before and after the counseling was carried out. The result achieved in this activity is that the people of Laikang Village understand the rules in managing and utilizing coastal areas so that disputes that lead to conflict can be minimized. — Ketidakpahaman masyarakat mengenai aturan batas pantai dan cara pengelolaan dan pemanfaatan wilayah pesisir banyak menimbulkan konflik antarwarga. Sementara itu, kesadaran nilai-nilai strategis dari pengelolaan wilayah pesisir secara berkelanjutan, terpadu dan berbasis masyarakat juga sangat kurang. Tujuan dari kegiatan pengabdian ini ialah meningkatkan pemahaman masyarakat mengenai pengaturan mengenai pengelolaan dan pemanfaatan wilayah pesisir sehingga dapat meminimalisir terjadinya sengketa yang berujung konflik antarwarga. Metode yang digunakan ialah metode penyuluhan hukum dengan menghadirkan langsung narasumber dari Kantor Pertanahan Kabupaten Takalar dan Akademisi yang merupakan pakar Pengelolaan Wilayah Pesisir. Tingkat keberhasilan kegiatan diukur dengan adanya kuesioner berupa pre test dan post test yang diberikan kepada peserta sebelum dan sesudah penyuluhan dilakukan. Hasil yang dicapai dalam kegiatan ini ialah masyarakat Desa Laikang memahami aturan dalam mengelola dan memanfaatkan wilayah pesisir sehingga sengketa yang berujung konflik dapat diminimalisir.